MEASURING HUMAN CAPITAL EFFICIENCY IN THE MALAYSIAN ENERGY SECTOR : A VALUE ADDED INTELLECTUAL CAPITAL (VAIC) APPROACH - Rozihanim Shekh Zain; Nor Julia Amira Nor Adzmi; Noor Sharida Badri Shah; Shaliza Azreen Mohd Zulkifli; Roslan Ja’afar (International Journal of Accounting, Finance and Business, 2024)
In the massive economic development, human capital plays as the most crucial assets exists within a firm to sustain the firm performance of the company. For the development of energy sector, it is vital to use certain resources. The purpose of this paper is to examine human capital efficiency in the Malaysian energy sector using the VAIC technique, which is the most widely used method for evaluating intellectual capital efficiency. The data collection for this study was acquired from the annual reports of Malaysian energy corporations from 15 companies from the energy sector within 2012 to 2021. The result indicates that Hengyuan Refining Company Berhad (HRCB) has the highest human capital efficiency score among energy firms followed by Deleum Berhad (DELEUM). The least efficient firms are Bumi Armada Berhad (BUMI ARMADA) followed by Dayang Enterprise Holdings Berhad (DAYANG) and Petra Energy Berhad (PETRA). Based on the findings, human capital efficiency affects profitability in different cases and relies more on the characteristics of the company itself. The characteristics or the nature of the organization has a greater impact on the decision to invest in human capital for the specific company. Different characteristics of the company's will result in a diverse pattern of intellectual capital investment decisions. Energy companies will be able to critically analyze the tactics they have used to increase human capital investment and create an effective strategies that can boost the sustainability and competitive advantage of the company which aligned with Environmental, Social and Governance (ESG) policy.